2011
DOI: 10.4049/jimmunol.1002030
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Allorecognition Has a Limited Impact on Posttransplant Vaccination

Abstract: Transplantation of allogeneic hematopoietic stem cells with or without immunocompetent lymphocytes has proved a successful strategy in the treatment of hematological malignancies. We have recently shown that this approach can also cure mouse prostate cancer, provided that it is combined with tumor-specific vaccination. Whether the response to alloantigens acts by providing helper function to enhance vaccine-specific responses or in other ways impinges on vaccine immunogenicity remains to be clarified, and this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
(53 reference statements)
2
7
0
Order By: Relevance
“…Of note, TRAMP recipients of male and female DLI responded equally well to the dendritic cell vaccine. This supports the notion that Tag-IV-specific T-cell priming was not influenced by concurrent alloreactivity, as we previously showed to be the case under tumor-free condition (25). Vaccine-induced T-cell responses in secondary lymphoid organs correlated with the onset of intratumoral proinflammatory responses.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Of note, TRAMP recipients of male and female DLI responded equally well to the dendritic cell vaccine. This supports the notion that Tag-IV-specific T-cell priming was not influenced by concurrent alloreactivity, as we previously showed to be the case under tumor-free condition (25). Vaccine-induced T-cell responses in secondary lymphoid organs correlated with the onset of intratumoral proinflammatory responses.…”
Section: Resultssupporting
confidence: 74%
“…Results depicted in Fig. 3 indicate that tumor-specific CTL accumulate to similar extents in the spleens of mDLI and fDLI TRAMP recipients, supporting the notion that alloreactive T cells do not contribute to Tagspecific T-cell priming (25). Analysis of UGA sections revealed the number of tumor-infiltrating CD3 þ cells, including both CD4 þ and CD8 þ T cells ( Supplementary Fig.…”
Section: Ifn-g-competent T Cells Are Required For Tumor Infiltration mentioning
confidence: 55%
See 1 more Smart Citation
“…Vaccines have demonstrated efficacy in the autologous setting in expanding T cells specific for tumor-associated antigens (TAA) and have the potential to enhance the graft-versus-leukemia (GVL) effect(11-18). We have previously demonstrated that even mild GVHD adversely impacts the magnitude of immune responses to a vaccine targeting antigens not expressed on normal host tissues(12) through an undefined mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that even mild GVHD adversely impacts the magnitude of immune responses to a vaccine targeting antigens not expressed on normal host tissues(12) through an undefined mechanism. Although the deleterious impact of GVHD on T cell populations as a whole has been well established, few studies have carefully characterized the effect of the alloreactive environment on non-alloreactive T cells responding to a vaccine(18, 19). In this report, we studied the capacity for vaccine-responding T cells with known antigen specificity toward non-allogeneic antigens to proliferate and survive in the setting of GVHD after MHC-matched, mHA-mismatched alloBMT.…”
Section: Introductionmentioning
confidence: 99%